Analysis of The Effect of Peer's Compliance Information on Tax Compliance Decisions - Irwan Aribowo; Nadia Fajriani; Laily Rofi’ah; Agus Suryono; Khairul Muluk; Andy Fefta Wijaya (Indonesian Association for Public Administration (IAPA), 2020)
Taxpayers are an important factor in the self-assessment system. The peer effect is one of the ways to gain taxpayers’ compliance. This study tries to explore the relationship between peer’s information and tax decisions on individual taxpayers. This study is based on experimental methods to determine the effect of information on individual behavior. The result showed that there was a significant influence between peer’s information and taxpayer decisions. Moreover, the compliance depends on what information is provided. The statistical method discovers that both filing and reporting information affect the taxpayer’s decisions. The Directorate General of Taxes can take advantage of peer’s information in conducting socialization and counseling in a segmented manner with the help of pillars of social norms. This action is expected to have an impact on individual taxpayers with the same background or level and is expected to create constant tax information in the near future.